2015
DOI: 10.1002/lary.25304
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical localization of OCT2 in the cochlea of various species

Abstract: ObjectiveTo locate the organic cation transporter 2 (OCT2) in the cochlea of three different species and to modulate the ototoxicity of cisplatin in the guinea pig by pretreatment with phenformin, having a known affinity for OCT2.Study DesignImmunohistochemical and in vivo study.MethodsSections from the auditory end organs were subjected to immunohistochemical staining in order to identify OCT2 in cochlea from untreated rats, guinea pigs, and a pig. In the in vivo study, guinea pigs were given phenformin intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…3B) and taken up by a variety of cochlear cells. Although it is unclear how transporters like OCT2 and CTR1 facilitate cisplatin trafficking through the cochlea, competitive inhibition of CTR1 and genetic loss of function in the OCT2 gene offer protection from cisplatin-induced ototoxicity (Ciarimboli et al, 2010; Hellberg et al, 2015; Lanvers-Kaminsky et al, 2015; More et al, 2010). Unlike most cells, sensory hair cells have mechano-electrical transduction (MET) channels that are uniquely gated by tip links between individual stereocilia in their apically-located hair bundle (Assad et al, 1991; Hudspeth, 1986; Hudspeth and Corey, 1977; Pickles et al, 1984).…”
Section: Cisplatin and Other Platinum Compoundsmentioning
confidence: 99%
“…3B) and taken up by a variety of cochlear cells. Although it is unclear how transporters like OCT2 and CTR1 facilitate cisplatin trafficking through the cochlea, competitive inhibition of CTR1 and genetic loss of function in the OCT2 gene offer protection from cisplatin-induced ototoxicity (Ciarimboli et al, 2010; Hellberg et al, 2015; Lanvers-Kaminsky et al, 2015; More et al, 2010). Unlike most cells, sensory hair cells have mechano-electrical transduction (MET) channels that are uniquely gated by tip links between individual stereocilia in their apically-located hair bundle (Assad et al, 1991; Hudspeth, 1986; Hudspeth and Corey, 1977; Pickles et al, 1984).…”
Section: Cisplatin and Other Platinum Compoundsmentioning
confidence: 99%
“…79 However, the antibody used in that study is probably nonspecific because control labeling of rat kidneys showed that OCT2 is localized in the apical membrane of renal tubules. 79 This localization is evidently false because OCT2 is well known to be expressed in the basolateral membrane domain. 80 Outer and inner hair cells, the stria vascularis, the spiral ganglia, and the surrounding nerves of the cochlea also express the CTR1.…”
Section: Platinum Derivativesmentioning
confidence: 90%
“…Recently, an immunohistological study of OCT2 expression in the rat cochlea failed to detect any expression of the transporter in hair cells or in the stria vascularis . However, the antibody used in that study is probably nonspecific because control labeling of rat kidneys showed that OCT2 is localized in the apical membrane of renal tubules . This localization is evidently false because OCT2 is well known to be expressed in the basolateral membrane domain .…”
Section: Chemotherapeutic Drugs That Interact With Transporters For Omentioning
confidence: 96%
See 1 more Smart Citation
“…In the article "Immunohistochemical localization of OCT2 in the cochlea of various species," which appeared in the September 2015 Issue of Laryngoscope, 1 Hellberg et al investigated the expression of the organic cation transporter 2 (Oct2) in the cochlea of different animals by immunohistochemical analysis. The issue is of importance because of the role of Oct2 as an uptake transporter for ototoxic and nephrotoxic drugs such as cisplatin, 2,3 and such an analysis has the potential to predict which cells are particularly sensitive to cisplatin toxicity.…”
Section: Letter To the Editormentioning
confidence: 99%